Structure, stratigraphy and tectonic evolution of the Ñirihuau basin in the río Cushamen region, Chubut - Ramos, M.E. (2011)
The southern part of the Ñirihuau basin at the valley of the Cushamen River region, is deformed and uplifted forming a prominent Precordillera Patagónica fold and thrust belt, east of the Patagonian Andes. The Ñirihuau Basin infill is represented by Oligocene to Miocene sedimentary to volcaniclastic rocks gathered in eleven litho types belonging to four members. These foreland sequences are exposed by a combination of thin-skinned deformation whose shortening is transferred to the basement in the west beneath the Cordón del Maitén. The entire Ñirihuau section as well as the overlying Collón Cura Formation is characterized by the occurrence of progressive unconformities, fact that implies synorogenic sedimentation at the time of the Cordón del Maitén range uplift. This belt is formed by an east-verging basement wedge associated with a series of backthrusts. The reactivation of the deformation associated with growth strata, indicates that the basin has evolved in a wedge-top of a foreland system in different pulses of deformation.